2015
DOI: 10.1007/s00436-015-4363-9
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo effectiveness of French over-the-counter products against head lice (Pediculus humanus capitis De Geer, 1778)

Abstract: Head lice infestation is still a public health problem worldwide, with an intracountry and intercountry prevalence variation of 0.7 to 59%. There is a large variety of over-the-counter anti-louse products, but their efficacy is not always well assessed. Our objective was to test the pediculicidal and ovicidal efficacy of 21 over-the-counter head louse products, available in France during the period of 2008 to 2012. We tested children living in Tours City in central France and visiting preschools, primary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The time for measurement of affected lice in a bioassay should consider the recovering of insects after the exposure treatment (Combescot-Lang et al, 2015). Thus, we considered 7 h after treatment as the observational reference period reliable to estimate pediculicidal effectiveness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time for measurement of affected lice in a bioassay should consider the recovering of insects after the exposure treatment (Combescot-Lang et al, 2015). Thus, we considered 7 h after treatment as the observational reference period reliable to estimate pediculicidal effectiveness.…”
Section: Methodsmentioning
confidence: 99%
“…Criterion of affected insects was according to Combescot-Lang et al (2015). Briefly, a louse was considered alive if it showed no symptoms or some abnormal movements and having difficulties turning over.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the emergence and spread of lice that are insensitive (resistant) to the active ingredient and/or formulation, existing pediculicides should be re‐evaluated every 5 years in ex vivo tests or clinical trials to document the actual level of efficacy they elicit 26 …”
Section: Recommendations For the Health Authoritiesmentioning
confidence: 99%
“…Various prevalence levels of pediculosis have been reported globally during the past two decades [ 2 , 6 , 14 , 28 – 30 ]. Recent studies on pediculosis have revealed that among Asian countries, the number of studies are overrepresented in Turkey and Iran.…”
Section: Introductionmentioning
confidence: 99%